2010
DOI: 10.1007/s11606-010-1538-z
|View full text |Cite
|
Sign up to set email alerts
|

Splenic Artery Pseudoaneurysm Complicating Pancreatitis

Abstract: A 62-year-old man with alcoholic cirrhosis was admitted for acute on chronic pancreatitis. During his last admission 3 months before, a CT scan had showed ascites as well as a 5.0-cm high-density posterior pancreatic tail fluid collection communicating with high-density material between the aorta and left renal vein (Fig. 1). The patient refused further workup and was discharged home. During this next admission, CT angiography showed an 8.6-cm partially thrombosed splenic artery pseudoaneurysm at the pancreati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 1 publication
1
12
0
Order By: Relevance
“… 7 , 14 , 18 The third trimester of pregnancy is the period with the highest risk. 1 Our literature survey revealed that among the 78 giant SAA cases, 8 had cirrhosis, 13 , 18 , 23 , 41 , 47 , 56 , 64 , 65 2 had portal hypertension, 14 and 1 had a history of pregnancy, 66 which are possible predisposing conditions for SAA. Relatively rare risk factors are splenomegaly, medial fibrodysplasia, arteritis, collagen vascular disease, polyarteritis nodosa, systemic lupus erythematosus, anomalous splenic artery origin, α 1 -antitrypsin deficiency, and inflammatory and infectious diseases.…”
Section: Discussionmentioning
confidence: 90%
“… 7 , 14 , 18 The third trimester of pregnancy is the period with the highest risk. 1 Our literature survey revealed that among the 78 giant SAA cases, 8 had cirrhosis, 13 , 18 , 23 , 41 , 47 , 56 , 64 , 65 2 had portal hypertension, 14 and 1 had a history of pregnancy, 66 which are possible predisposing conditions for SAA. Relatively rare risk factors are splenomegaly, medial fibrodysplasia, arteritis, collagen vascular disease, polyarteritis nodosa, systemic lupus erythematosus, anomalous splenic artery origin, α 1 -antitrypsin deficiency, and inflammatory and infectious diseases.…”
Section: Discussionmentioning
confidence: 90%
“…Splenic artery aneurysms are up to 4 times more common in females while overall incidence increases to 10% in patients > 60 years and in patients with portal hypertension [12,13]. Spontaneous rupture is associated with high mortality, up to 40% for true aneurysms, and even 90% for PSAs [8,9,10]. In patients with intraperitoneal SAA rupture, acute abdomen and hypovolemic shock, splenectomy and SA ligation are mostly performed [14,15].…”
Section: Discussionmentioning
confidence: 99%
“…Pancreatitis, on the other hand, has been associated with SA pseudoaneurysm development with high risk of rupture up to 40% and mortality up to 90% [10,16]. It has been proposed that in the case of pancreatitis, pancreatic enzymes are responsible for destruction of arterial wall architecture and disintegration of elastic tissues, leading to formation of pseudoaneurysm [17].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Splenic infarction occurs in case of occlusion of the splenic vascular supply, leading to tissue ischemia and necrosis. Thromboembolism is the most common cause of splenic infarctions [12][13][14][15]. Splenic infarction may be due to arterial or venous occlusion.…”
Section: Discussionmentioning
confidence: 99%